An efficient RNA-seq-based segregation analysis identifies the sex chromosomes of Cannabis sativa - Prentout, Djivan; Razumova, Olga; Rhoné, Bénédicte; Badouin, Hélène; Henri, Hélène; Feng, Cong; Käfer, Jos; Karlov, Gennady; Marais, Gabriel A.B. (Genome Research, 2020)
Cannabis sativa–derived tetrahydrocannabinol (THC) production is increasing very fast worldwide. C. sativa is a dioecious plant with XY Chromosomes, and only females (XX) are useful for THC production. Identifying the sex chromosome sequence would improve early sexing and better management of this crop; however, the C. sativa genome projects have failed to do so. Moreover, as dioecy in the Cannabaceae family is ancestral, C. sativa sex chromosomes are potentially old and thus very interesting to study, as little is known about old plant sex chromosomes. Here, we RNA-sequenced a C. sativa family (two parents and 10 male and female offspring, 576 million reads) and performed a segregation analysis for all C. sativa genes using the probabilistic method SEX-DETector. We identified >500 sex-linked genes. Mapping of these sex-linked genes to a C. sativa genome assembly identified the largest chromosome pair being the sex chromosomes. We found that the X-specific region (not recombining between X and Y) is large compared to other plant systems. Further analysis of the sex-linked genes revealed that C. sativa has a strongly degenerated Y Chromosome and may represent the oldest plant sex chromosome system documented so far. Our study revealed that old plant sex chromosomes can have large, highly divergent nonrecombining regions, yet still be roughly homomorphic.